The Future Generation Intelligent System Need For Human Memory To Detect Crime Using Virtual Brain Technology. (International Journal of Engineering and Computer Science, 2015)
In this paper we have suggested an idea to detect the crime of the human by using virtual brain technology. Human brain is the most valuable creation of the god in the  world but” Virtual brain” or virtual brain that means a machine can act as a human brain, it can think, take decision and respond, a machine can function as a human brain. The unique identity of the human being is their own creative knowledge.  After death, it will get destroyed. But we will recreate their knowledge using virtual brain technology.   Simply we called it as virtual brain. The Virtual brain is an attempt to reverse engineering the human brain and recreate it at the cellular level inside a computer simulation. After the death of the body, the virtual brain will act as a man.  So, even after the death of the person we will not loose the knowledge, intelligence, personalities, feelings and memories of the human.